Scattering processes of helium nuclides on nuclei 28Si - Sadykov, B.M.; Nassurlla, M.; Duisebayev, B.A.; Zholdybayev, T.K.; Sakuta, S.B.; Bugybayev, Y. (Recent Contributions to Physics, 2021)
Experimental data on elastic and inelastic scattering of 50.5 MeV α-particles and 60 MeV 3He ions by 28Si nuclei were analyzed within the framework of the standard optical model of the nucleus, in which the effect of inelastic channels is taken into account by the phenomenological introduction of an imaginary absorbing part into the interaction potential between colliding nuclei. The optimal values of the internuclear interaction potential obtained as a result of the theoretical analysis were used to study the cross sections for inelastic scattering of helium ions with the excitation of the 1.78 and 4.61 MeV states of the nucleus under study. From the analysis by the channel coupling method, where the calculation was performed taking into account both elastic and inelastic channels, the value of the quadrupole deformation parameter for α-particles β2 = 0.37 and for 3He ions β2 = 0.49 was determined. Optimal agreement between the calculated values and experimental data was achieved by varying the parameters V, W, and β2. The found parameters agree with the previously obtained values from the scattering of protons, deuterons and α-particles. Taking into account only the quadrupole deformation extracted from the 0+ – 2+ bond, a good description of all three experimental data on elastic and inelastic scattering of the cross sections was achieved.
Keywords: elastic and inelastic scattering; optical model; optical potential; coupled channel method